Effect of profiled decking on composite beam-column joints with end-plate bolted connections under column-removal scenario - Chen, Shuang (2022)
In the design of structures against progressive collapse, component-based modelling has been applied to simulate the behaviour of beam-column joints under column-removal scenarios. However, only limited studies consider the effect of profiled decking on load-carrying capacity of composite joints. In composite frames, the direction of profiled sheeting is parallel to the main beam but runs transverse to supporting secondary beams. This study aimed to develop component-based models that can predict behaviour of beam-column joints with either longitudinal or transverse profiled sheeting so that engineers can design joints on both the main and the secondary beams against progressive collapse. Two composite beam-column joints with extended end-plate (EEP) connections and two with partial-depth end-plate (PEP) connections were tested under a central-column-removal scenario. For each connection type, both longitudinal and transverse profiled sheeting directions were studied. Two welded T-stub specimens were tested to obtain the behaviour of component properties. Innovative component models for concrete components and for welded T-stubs in extended end-plate joints were developed. The proposed component-based models gave acceptable predictions of composite joint behaviour. It was found that extended end-plate connections had better load-carrying capacity but lower joint rotation capacity than partial depth end-plate connections. For the same connection type (either EEP or PEP), the maximum loads of specimens with transverse sheeting were only 70% of those with longitudinal sheeting.